The CD45 locus in cattle: Allelic polymorphism and evidence for exceptional positive natural selection - Ballingall, Keith T.; Waibochi, L.; Homes, E.C.; Woelk, C.H.; MacHugh, Niall D.; Lutje, V.; McKeever, Declan J. (Springer, 2001)
Cattle in Africa are a genetically diverse population that has resulted from successive introduction of Asian Bos indicus and European B. Taurus cattle. However, analysis of mitochondrial genetic diversity in African cattle identified three lineages, one associated with Asian B. indicus, one with European B. Taurus, and a third ascribed to an indigenous African sub-species of cattle. Due to their extended co-evolution indigenous African herbivores are generally tolerant to endemic African pathogens. We are intertolerant to endemic African pathogens. We are interested in identifying alleles derived from the indigenous African cattle that may be associated with tolerance to African pathogens. An analysis of the locus which encodes the abundant plasma membrane-associated tyrosine phosphatase. CD45, identified three highly divergent allelic families in Kenya Boran cattle. Analysis of allelic distribution in a diverse range of cattle populations suggests a European B. taurus, an Asian B. indicus, and an African origin. This demonstrates not only significant allelic polymorphism at the CD45 locus in cattle but also convincing autosomal evidence for a distinct African sub-species of cattle. Furthermore, maximum-likelihood analysis of subject to exceptionally strong natural selection which we suggest may be pathogen driven.